Identification of Polymorphic Outer Membrane Proteins of Chlamydia psittaci 6BC - Tanzer, Regina J. (American Society for Microbiology, 2001)
The genomes of Chlamydia spp. encode a family of putative outer membrane proteins, referred to as polymorphic outer membrane proteins (POMPs), which may play a role in the avoidance of host immune defenses. We analyzed avian strain 6BC of Chlamydia psittaci by polyacrylamide gel electrophoresis for the expression of POMPs. At least six putative POMPs were identified on the basis of their size (90 to 110 kDa) and labeling with an outer membrane-specific probe, 3-(trifluoromethyl)-3-(m-[(125)I]iodophenyl)diazirine. Three of the putative POMPs reacted with antiserum raised against a recombinant ovine C. psittaci strain POMP, and two possessed surface-exposed, trypsin-sensitive sites. The POMPs were dependent on disulfide bonds for their maintenance in sodium lauryl sarcosine- and sodium dodecyl sulfate-insoluble complexes but did not appear to be interpeptide disulfide bond cross-linked. The putative POMPs were found to be synthesized during the late phase of the chlamydial developmental cycle, cotemporally with the cysteine-rich doublet periplasmic proteins.